2012
DOI: 10.4236/jgis.2012.44042
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Indigenous Knowledge and Geo-Informatics for Water Harvesting Siting in the Jordanian Badia

Abstract: Jordan is located in an arid to semi arid region where around 90% of its land receives an average annual precipitation of less than 100 mm while only 3% of the land receives an average annual precipitation of 300 mm or more. Jordan is characterised as a “water scarce” country because the current <i>per capita</i> share of water is estimated to be of the order of 140 m<sup>3</sup> per year which is well below the 1000 m3 threshold. Rainwater harvesting is the accumulating and storing, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 20 publications
(30 reference statements)
0
46
0
3
Order By: Relevance
“…Due to long drought periods and over utilizing of range lands in the arid lands of Jordan, the land is degraded and lost most of its natural vegetation [2]. To rehabilitate the natural vegetation cover, there is a need to enhance the fertility of soil to be able to support vegetation under limited amounts of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Due to long drought periods and over utilizing of range lands in the arid lands of Jordan, the land is degraded and lost most of its natural vegetation [2]. To rehabilitate the natural vegetation cover, there is a need to enhance the fertility of soil to be able to support vegetation under limited amounts of rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Upper East Region of Ghana, these factors failed to present specific constraints in siting irrigation dams and therefore were not used in this research. Research by Al-Adamat et al (2012) indicated that dams are usually built on rivers and human activities have had a profound impact on river systems throughout the world. Proper investigation, interpretation, and analyses of different terrain parameters such as elevation, topography, and slope instability of the dam site hold the key for the success of the dam in terms of economic sustainability and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Proper investigation, interpretation, and analyses of different terrain parameters such as elevation, topography, and slope instability of the dam site hold the key for the success of the dam in terms of economic sustainability and durability. Geo-spatial techniques will provide not only fast and accurate data, but also reliable data, which can be further analyzed in order to give the complete picture of the dam site (Al-Adamat et al, 2012). According to Singh, Darshdeep, and Lorita (2008), in India, criteria such as slope, land use, soil infiltration rate, and soil type have been used for making decision in selecting a suitable site for various water harvesting structures as per Integrated Mission for Sustainable Development (IMSD).…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this study was to define a general method for selecting suitable RWH sites in ASARs based on methods developed throughout the last three decades. The success of RWH systems depends heavily on the identification of suitable sites and on their technical design (Al-Adamat et al, 2012). The 48 articles we reviewed indicated that the way sites are selected has shifted over time, reflected in the three sets of guidelines: IMSD, (1995), and FAO (2003) (see Table 2.2).…”
Section: Discussionmentioning
confidence: 99%
“…The success of RWH systems depends heavily on the identification of suitable sites and their technical design (Al-Adamat et al, 2012). Various methodologies have been developed for the selection of suitable sites and techniques for RWH (Ahmad, 2013;Al-Adamat, 2008;De Winnaar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%